2022
DOI: 10.3390/ani12182416
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Oncolytic Pseudorabies Virus Vaccine Strain Inhibited the Growth of Colorectal Cancer HCT-8 Cells In Vitro and In Vivo

Abstract: Oncolytic viral therapy is a promising treatment approach for a variety of tumor forms. Although a number of studies have demonstrated that the pseudorabies virus (PRV) may be applied as an oncolytic carrier, the anti-colorectal cancer impact of the virus and the mechanism of its cytotoxic effect remain elusive. In this study, the replication capacity and cell activity of PRV attenuated live vaccines Bartha K61 and HB98 in HCT-8 cells in vitro were investigated. Next, the antitumor ability and safety were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Presently, research regarding oncolytic viruses employing PRV as a vector is relatively scarce, with studies primarily conducting in vitro and in vivo tests using a virulence-gene-knockout PRV [ 5 , 7 , 18 ]. In this study, we used PRV as an oncolytic virus vector and carried out genetic engineering to construct PRV recombinant viruses carrying anti-tumor genes for the first time and verified their therapeutic effect on the mouse pancreatic cancer tumor model.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Presently, research regarding oncolytic viruses employing PRV as a vector is relatively scarce, with studies primarily conducting in vitro and in vivo tests using a virulence-gene-knockout PRV [ 5 , 7 , 18 ]. In this study, we used PRV as an oncolytic virus vector and carried out genetic engineering to construct PRV recombinant viruses carrying anti-tumor genes for the first time and verified their therapeutic effect on the mouse pancreatic cancer tumor model.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that PRV-IE180 has the capacity to eliminate various types of tumor cells in vitro [ 10 ]. In addition, PRV with deleted TK , gE and gI virulence genes has been reported to possess the ability to impede tumor growth and prolong the survival time of mice in bladder cancer and colon cancer models, while simultaneously considering the efficacy and safety of oncolysis [ 5 , 19 ]. Our study also showed that the PRV with the TK , gG , gE and gI virulence genes deleted was effective in killing four tumor cell lines, including Pan02, EMT-6, CT26 and H446, thereby expanding the oncolytic spectrum of PRV in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations